Mechanisms of disease: hypertrophic cardiomyopathy - Frey, Norbert; Lüdde, Mark; Katus, Hugo (Nature reviews. Cardiology, 2012)
Hypertrophic cardiomyopathy (HCM) is the most-common monogenically inherited form of heart disease, characterized by thickening of the left ventricular wall, contractile dysfunction, and potentially fatal arrhythmias. HCM is also the most-common cause of sudden cardiac death in individuals younger than 35 years of age. Much progress has been made in the elucidation of the genetic basis of HCM, resulting in the identification of more than 900 individual mutations in over 20 genes. Interestingly, most of these genes encode sarcomeric proteins, such as myosin-7 (also known as cardiac muscle β-myosin heavy chain; MYH7), cardiac myosin-binding protein C (MYBPC3), and cardiac muscle troponin T (TNNT2). However, the molecular events that ultimately lead to the clinical phenotype of HCM are still unclear. We discuss several potential pathways, which include altered calcium cycling and sarcomeric calcium sensitivity, increased fibrosis, disturbed biomechanical stress sensing, and impaired cardiac energy homeostasis. An improved understanding of the pathological mechanisms involved will result in greater specificity and success of therapies for patients with HCM.